PENILAIAN EFEKTIVITAS PUPUK ANORGANIK NPK 12-10-22 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS - Diaguna, Ridwan; Suwarto, Suwarto; Sularno, Sularno; Sarjani, Alvita Sekar (JURNAL AGROTROPIKA, 2025)
The utilization of NPK fertilizer specifically formulated to meet the requirements of maize plants can contribute to improved nutrient absorption efficiency and maximized growth and yield. Choosing NPK fertilizer with a suitable nutrient content is a critical aspect in attaining optimal maize productivity. This study aimed to determine the effectiveness of inorganic NPK 12-10-22 fertilizer on the growth and yield of sweet corn (Zea mays saccharata L.). This study was conducted from November 2022 to February 2023 at the Sawah Baru Experimental Garden, Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University, Bogor, West Java. The study was arranged in a randomized complete block design with four replications. The fertilizer dose treatments consisted of six levels: without the tested fertilizer application (Control), Standard NPK fertilizer as a comparison (Standard NPK), 0.5 doses of NPK 12-10-22 (0.5 NPK), 1.0 dose of NPK 12-10-22 (1.0 NPK), 1.5 doses of NPK 12-10-22 (1.5 NPK), and 2.0 doses of NPK 12-10-22 (2.0 NPK). The application of 0.5 to 2.0 doses of inorganic NPK 12-10-22 fertilizer was able to produce growth characteristics, yield components, and yields of sweet corn plants that were equally as good as the standard treatment. The application of 2.0 doses of NPK 12-10-22 fertilizer even resulted in significantly higher cob weight and cob weight without husk compared to the standard dose. The application of 1.0, 1.5, and 2.0 doses of inorganic NPK 12-10-22 fertilizer produced RAE (Relative Agronomic Efficiency) values ≥ 95%, namely 111%, 104%, and 125% for sweet corn plants. The recommended dose of NPK 12-10-22 fertilizer is 545.5 kg per hectare, accompanied by 161 kg of urea, 48 kg of SP-36, and 80 kg of KCl per ha.